Diagnosis of endometrial pathologies: transvaginal sonography versus hysteroscopy - Çetin, Berna Aslan; Beyaz, Ayşe; Türkgeldi, Lale S.; Bahat, Pınar Yalçin; Köroğlu, Nadiye (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) constitutes 69% of all gynecological complaints in the peri- and postmenopausal age groups. The aim of present study was to compare the accuracy of transvaginal sonography and hysteroscopy in diagnosing intracavitary pathologies in women with abnormal uterine bleeding. Methods: A total of 303 premenopausal women with abnormal uterine bleeding who admitted to the gynecology outpatient clinic of the Istanbul Kanuni Sultan Suleyman Research and Training Hospital, Istanbul, Turkey, between April 2010 and July 2015, and received hysteroscopy, were evaluated retrospectively. The collected data were assembled from the computerised database. All patients underwent pelvic examination, transvaginal ultrasonography, office hysteroscopy and hystopathologic evaluation. Patients with normal appearing uterine cavities on hysteroscopy additionally underwent full curettage. The pathology reports were considered to be the definitive diagnoses of patients. Transvaginal ultrasonography and office hysteroscopy findings were compared with the pathological reports and the sensitivity, specificity, positive and negative predictive values, accuracy values and likelihood ratios of office hysteroscopy and transvaginal ultrasonography were calculated for the detection of endometrial abnormalities. Results: Endometrial polyps were the most commonly identified pathology with a rate of 77.56%. The sensitivity, specificity, positive and negative predictive values of transvaginal sonography for diagnosing endometrial pathologies were 77%, 32%, 75% and 32%, respectively. The same values for hysteroscopy were 93%, 44%, 88% and 48% respectively. Transvaginal sonography had a sensitivity of 20% with a specificity of 4% for submucous myomas. The sensitivity, specificity, positive and negative predictive values of hysteroscopy for submucous myomas when compared to histopathology were 100% for all. Conclusions: The diagnostic accuracy of office hysteroscopy for focal lesions such as polyps or submucous myomas is higher than the accuracy of transvaginal ultrasonography. Due to its high diagnostic accuracy, lower complication rate and the ability to obtain direct biopsy specimens while providing simultaneous treatment, we believe that hysteroscopy will retain its place as the gold standard procedure for the investigation of endometrial pathologies.